Pembinaan Tahsin Alquran dengan Metode Tilawati bagi Mahasiswa Hukum Tata Negara Fakultas Syariah IAIN Langsa - Muhazir Muhazir (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2022)
The Quran became an identity for the Islamic community because the Quran was the principal source of law in Islam. The ability to read the Quran is one of the benchmarks for understanding the content of the Quran. The ability to read the Quran for sharia faculty students has become a must, good and correct reading quality following the rules of tajweed science is an identity for sharia faculty students, even students who have not been able to read the Quran will be sanctioned in the form of not being able to take part in the thesis trial. This guidance is carried out to see and improve students' ability to read the Quran and provide guidance for those who have not been able to read the Quran well. The method used in this research is Participatory Action Research (PAR) because in this study the researcher is directly involved in coaching activities. This coaching is carried out for one month with a duration of 16 face-to-face meetings with the number of fostered participants reaching 20 students. The results of this guidance illustrate that Constitutional Law students have increased in learning using the tilawat method. The increase can be seen from the value obtained during the pre-test and post-test. this method is very suitable for learning the Quran because this method combines the science of recitation, makhroj, and recitations by following the science of recitation. The stages used in this coaching method consist of 3 stages; first, learning makhroj; second, learning recitation; third, recitations. While the coaching model is in the form of a class with the classical method, namely the teacher reads the student's following.